2009
DOI: 10.1007/bf03345749
|View full text |Cite
|
Sign up to set email alerts
|

B-type natriuretic peptide levels and insulin resistance in patients with severe ischemic myocardial dysfunction

Abstract: B-type natriuretic peptide (BNP) is an important clinical parameter of severity in congestive heart failure (CHF). Recent findings suggest a close relation between lipid and glucose metabolism and the natriuretic peptide axis, even if conflicting data exist on the relationship between natriuretic peptide levels and insulin resistance (IR). Thus, we sought to investigate potential relations between BNP level and IR in 134 patients with severe ischemic myocardial dysfunction [mean+/-SD: age =64.8+/-9.6 yr, male/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Plasma BNP/NT-proBNP values are inversely related to body mass index (BMI) in both healthy subjects and patients with heart failure (Hubert et al, 1983;Clerico et al, 1999;Taylor et al, 2006;Tosa et al, 2009;Clerico et al, 2012). Several studies have reported various association of natriuretic peptides levels with insulin resistance (Olsen et al, 2005;Alcelik et al, 2007;Wang et al, 2007;Tassone et al, 2009). Recently, Khan et al (2011) reported that natriuretic peptide levels are lower both in non-obese and obese patients with insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma BNP/NT-proBNP values are inversely related to body mass index (BMI) in both healthy subjects and patients with heart failure (Hubert et al, 1983;Clerico et al, 1999;Taylor et al, 2006;Tosa et al, 2009;Clerico et al, 2012). Several studies have reported various association of natriuretic peptides levels with insulin resistance (Olsen et al, 2005;Alcelik et al, 2007;Wang et al, 2007;Tassone et al, 2009). Recently, Khan et al (2011) reported that natriuretic peptide levels are lower both in non-obese and obese patients with insulin resistance.…”
Section: Introductionmentioning
confidence: 99%